One-pass arc welding under thin slag layer of thick 09G2S steel plate structures - Yu. V. Poletaev; V. Yu. Poletaev (Advanced Engineering Research)
Introduction. The technology of single-pass arc welding under a thin layer of slag (AST) of thick plate welded structures in the thermal and nuclear engineering is considered. The structure material is 09G2S steel. The work objective is the experimental study on the applicability of the AST method instead of the automatic welding under flux (AWF) and electroslag welding (ESW) under manufacturing the package units of the power plants.Materials and Methods. The technology is developed on the basis of the calculation results of the thermal welding mode (thermal cycle parameters and welding mode settings). Test joint weld-samples, 100 mm thick, are made of 09G2S lowcarbon low-alloy steel. Welding is performed on the certified equipment of “EMC-Atommash” JSC. The welded joints quality is assessed on the standard control results by the following techniques: magnetic-particle testing (MPT), ultrasonic control (USC) and radiographic testing (RT). The non-destructive testing results were supplemented with the metallographic study data. To investigate the nature of the weld metal crystallization along the length of the weld, the macrotemplates were cut out mechanically from the middle through-the-thickness and at the distance of 10 mm from the surface. The technique and installation of “TCS-1” for simulating the thermal cycle of the metal welding of the heat affected zone (HAZ) of the welded joints; standard methods for determining mechanical properties; hardness and microhardness indices; and method for determining the grain size in micrographs according to GOST 5639-82 were used in the experiments. The microstructure was studied with MMP-2P and Reichert optical microscopes with increase up to thousandfolds. Besides, the distribution pattern and identification of the second phases of nonmetallics; welded samples and samples modeling the HAZ metal for the notch sensitivity; structure stability and welding cracking resistance were studied through the replica technique using the EMV-100LM electron microscope.Research Results. Based on the thermal calculation results and the HAZ metal modeling, the optimum values of the heat input and welding variables are validated and experimentally verified. The welded joints quality is estimated by the nondestructive and destructive methods. The effect of the welding method on the structure, quality and mechanical properties of the welded joints is established.Discussion and Conclusions. Positive results of the theoretical and experimental studies are obtained. They indicate the technological and economic efficiency of the AST method application (instead of AWF and ESW) under manufacturing the 100 mm thick welded joints of 09G2S low-alloy steel. Moderate heat input in AST allows for the one-pass forming of a welded joint with better fine-grained structure and higher mechanical characteristics as compared to the ESW and AWF. Recommendations on the use of the AST technique in the welding production are given.